Iceland : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2012)
This selected issues paper on Iceland reports that since mid-2009, Iceland has undergone a heavily frontloaded fiscal consolidation program to bring government finances to a sustainable level. To maintain the adjustment gains achieved during the last 2 1\2 years, the authorities have started drafting a new organic budget law, which would codify recent reforms in the budget framework and introduce principles for fiscal policymaking. Iceland's economy is exposed to adverse shocks. The external outlook continues to pose challenges, as key trading partners face weak growth prospects.